2004
DOI: 10.1074/jbc.m410077200
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Regulation of Low Density Lipoprotein Receptor Protein by Proprotein Convertase Subtilisin/Kexin Type 9a in Mouse Liver

Abstract: Lipid homeostasis is transcriptionally regulated by three DNA-binding proteins, designated sterol regulatory element-binding protein (SREBP)-1a, -1c, and -2. Oligonucleotide arrays hybridized with RNA made from livers of transgenic SREBP-1a, transgenic SREBP-2, and SREBP cleavage-activating protein knockout mice recently identified 33 genes regulated by SREBPs in liver, four of which had no known connection to lipid metabolism. One of the four genes was PCSK9, which encodes proprotein convertase subtilisin/kex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
412
2
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 469 publications
(447 citation statements)
references
References 45 publications
27
412
2
6
Order By: Relevance
“…Overexpression of WT PCSK9 reduced hepatic LDLRs to a similar extent as expression of PCSK9 mutant forms (7). These studies suggested that PCSK9 might function normally to reduce LDLR expression levels in liver.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Overexpression of WT PCSK9 reduced hepatic LDLRs to a similar extent as expression of PCSK9 mutant forms (7). These studies suggested that PCSK9 might function normally to reduce LDLR expression levels in liver.…”
mentioning
confidence: 55%
“…Recent studies suggest that hepatic LDLRs also may be posttranscriptionally regulated by proprotein convertase subtilisin͞ kexin type 9a (PCSK9) (5)(6)(7). PCSK9 belongs to the proteinase K subfamily of subtilases, which are proteinases synthesized as soluble zymogens that subsequently undergo autocatalytic cleavage to active enzymes (8).…”
mentioning
confidence: 99%
“…Pcsk9 overexpression in wild-type mice caused a two-fold increase in plasma total cholesterol and a five-fold increase in non-HDL cholesterol whereas overexpression of Pcsk9 had no effect on LDLR mRNA levels [Maxwell and Breslow, 2004]. Similarly to wild type, human mutant PCSK9 (p.S127R and p.F216L) overexpressed in the liver of mice leads to hypercholesterolemia due to a dramatic decrease of hepatic LDL receptor levels through a posttranscriptional mechanism [Park et al, 2004]. Conversely, livers of knockout mice lacking PCSK9 (Pcsk9-/-) display increased LDL receptor (but not mRNA) that leads to a decrease in plasma cholesterol levels of 48% compared to wildtype litter mates [Rashid et al, 2005].…”
Section: Functional Features Of Pcsk9 Variants Animal and Cellular Momentioning
confidence: 99%
“…10 -12 In mice the overexpression of wild-type PCSK9, as well as of mutant PCSK9 associated with hypercholesterolemia, resulted in a marked reduction of hepatic LDLreceptor (LDL-r) protein leading to hypercholesterolemia. [13][14][15] Missense mutations of PCSK9 associated with hypercholesterolemia in humans would increase the capacity of PCSK9 to limit the number of LDL-r, thus representing gain of function mutations. In sharp contrast, mice with targeted inactivation of PCSK9 gene (pcsk9 Ϫ/Ϫ ) have an increased number of LDL-r in the liver, increased removal of plasma LDL, and reduced plasma LDL-C. 16 In 2005 Cohen et al 17 found that 2 inactivating mutations of PCSK9 (Y142X and C679X), present in 2% to 2.6% of blacks of the Dallas Heart Study, were associated with 30% to 40% reduction of plasma LDL-C.…”
mentioning
confidence: 99%